The age and foreign language studying - Шевченко, С. П.; Shevchenko, S. (My University, 2015)
Today, the good command of a foreign language is very important for the success in many spheres of modern life. The more languages we can speak, the more successful we are. The people of different ages were taught by me (from 3 to 55 years old). Every age is unique. It’s necessary to find the special ways, methodology, individual findings for the student of every age. Let’s divide the people into three age categories. The first is the category of children (1-12 years old), the second is the category of teenagers and youth (13-25 years old), and the third is the category of grown ups (30 years old and older).
Keywords: foreign language